E-5: HAFIZ AL-HADITH DISCIPLES AND CONTEMPORARIES WHO HEARD HADITH FROM IMAM ABU HANIFA - Shaikh, Muhammad Shahzad; Nazir, Muhammad Irfan; Saeed, Muhammad Hassan (International Journal of Islamic Business, Administration and Social Sciences (JIBAS), 2024)
The authenticity of a Ṣaḥīḥ Ḥadīth regarding the narrator depends upon two basic characteristics in him: his strength of memory and his veracity. Regarding their memory, the narrators are generally categorized as a. Musnid, b. Muḥaddith, c. Mufīd, d. Ḥāfiẓ and e. Amīr ul-Muʾminīn fī Al-Ḥadīth. Category e, which consists of around 26 narrators only, is considered the most prestigious of the categories. The second-best category is that of Ḥāfiẓ Al-Ḥadīth. This paper studies the great contribution of Imām Abū Ḥanīfa and his students to memorize the Ḥadīth. Those scholars were Ḥāfiẓ Al-Ḥadīth as well as the students of Imām Abū Ḥanīfa and most of them were the initial followers of Ḥanafī school of thought. Several renowned scholars of their time have had the privilege of being Imām Abū Ḥanīfa’s disciples which greatly acknowledges the supremacy of Imām Abū Ḥanīfa in the science of Ḥadīth.